Locus standi in environment law; a comparative analysis of South Africa and the United States - Bohne, Jochen (Centre for Law and Society, 2026)
Due to the growing awareness of the impact of human activity on the ecology, the legislators around the world increasingly deal with the issue of environmental protection. In South Africa, there is already a considerable body of legislation that is concerned with the control of activities affecting the. environment. Those statutes may serve as a ground for concerned individuals or groups to approach a court in cases of alleged irregular or illegal acts. Privates may sue other privates for their illegal acts. They may also impugn the performance of public officials that are in charge of controlling polluting activities. A third option was opened up by amendments to the Environment Conservation Act 73 of 1989. Section 3 (2), which obliges the Director-General to ensure compliance of other state officials with the Department's declared policy. Thus, litigants are now able to claim a mandatory order compelling the Director-General to fulfil such duty. However, before an aggrieved individual or group may approach a court for judicial relief, certain requirements must be met. A major requirement which applies to all applicants who approach a court, is that they must have the legal standing - locus standi - in order to present their case. A feature of almost all legal systems is that an applicant is required to have a sufficient interest in the matter to claim legal standing. The locus standi is the threshold question for the justiciability of a case. The locus standi requirement must be dealt with before a decision is reached on the merits of the case. Why? then, is the locus standi question a particular issue for environmental lawyers? The locus standi requirement is applicable here as in any other field of law. However, the environment is a very general interest. Its degradation affects all who live in it. Yet, it is particularly the field of environmental law where illegal activities affecting the environment do not always have a direct impact on the interests of an individual or organisation. In case of those diffuse interests as protection of the environment, it becomes necessary to open up access to judicial resources to a broader range of potential litigants than under traditional locus standi rules. Moreover, it is especially the field of environmental law, where the implementation of statutes has often been seen unsatisfactory. C. Loots observes that South Africa's environmental legislation, generally speaking, has not been enforced effectively.1 Administrative officials of the various departments "seem to adopt a conciliatory rather than confrontational approach to polluters, which is evidenced by the fact that, with the exception of the Department of Water Affairs, they have initiated virtually no prosecutions.